Molecular phylogenetic analysis of subfamilial placement of Haplotropis Saussure, 1888 (Orthoptera: Pamphagidae) based on mitochondrial and nuclear DNA markers - Sukhikh, Igor; Blinov, Alexander; Bugrov, Alexander (Zootaxa, 2019)
The genus Haplotropis Sauss. is a relatively small genus in the family Pamphagidae (Orthoptera: Caelifera). Historically, there has been a discussion on the placement of this genus, whether it belongs in the subfamily Pamphaginae or in the subfamily Thrinchinae. Here we present a phylogenetic analysis of nucleotide sequences of two mitochondrial genes (COI, COII) and the ITS2 rRNA nuclear region of multiple species of the family Pamphagidae and related taxa. Our results clearly support the placement of the genus Haplotropis, and other species of the tribe Haplotropidini, in the subfamily Thrinchinae.